2016
DOI: 10.1111/cbdd.12906
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MicroRNA‐320d predicts poor overall survival and promotes the growth and invasive abilities in glioma

Abstract: Previous studies have demonstrated that miRNAs play an important role in tumor development and progression. The role of miR-320d has been studied in several cancers except for glioma. The aim of the study was to investigate the expression levels, biological function, and mechanism of miR-320d in glioma. The expression levels of miR-320d were detected in glioma tissues and cell lines (U87 and U251) by RT-qPCR. Cell proliferation, colony formation, apoptosis, cell cycle, and transwell assays were performed in gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Although recent studies have reported the functions of miR-320d in several cancer types, such as colorectal cancer [15], renal cell carcinoma [16], glioma [23], et al, less studies are focusing on the potential targeted genes of miR-320d. As the classical function of microRNA is silencing targeted genes by completely or incompletely pairing to the 3′-UTR of the specific genes, we screened the miR-320d targeted genes through the TargetScan website and other microRNA databases, and eventually found that FoxM1 contains two mRNA 3′-UTR binding sites for miR-320d.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have reported the functions of miR-320d in several cancer types, such as colorectal cancer [15], renal cell carcinoma [16], glioma [23], et al, less studies are focusing on the potential targeted genes of miR-320d. As the classical function of microRNA is silencing targeted genes by completely or incompletely pairing to the 3′-UTR of the specific genes, we screened the miR-320d targeted genes through the TargetScan website and other microRNA databases, and eventually found that FoxM1 contains two mRNA 3′-UTR binding sites for miR-320d.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that miR-1290 and miR-320d were significantly dysregulated in various cancers, including CRC10-14. Mao et al declared that miR-1290 functions as a tumor oncogene to promote cancer progression by targeting nuclear factor I/X (NFIX) in esophageal squamous cell carcinoma (ESCC)15; Ma et al reported that miR-1290 expression increases in CRC tissues and could contribute to cancer cell proliferation by targeting inositol Polyphosphate 4-Phosphatase B (INPP4B) 16; Tadano et al demonstrated miR-320 family, including miR-320a, miR-320b, miR-320c, miR-320d, and miR-320e, were frequently downregulated in colorectal adenoma and submucosal invasive carcinoma tissues and regulated tumor proliferation by targeting CDK6 17; In addition, Qin et al revealed that the expression of miR-320d is significantly decreased in glioma tissues and cell lines and overexpression of miR-320d could suppress cell growth, migration and invasion, and induce cell apoptosis as well as cell cycle at G0/G1 arrest18. Similarly, our results exhibited that circulating miR-1290 was significantly associated with tumor size, TNM stage, lymph node metastasis, and distant metastasis, and circulating miR-320d was significantly correlated with tumor size, advanced TNM stage, lymph node metastasis, and distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, the expression pattern and biological function of miR-320d in breast cancer are largely unknown.…”
Section: -10mentioning
confidence: 99%
“…Previous studies have reported the function of miR-320d in glioma, colorectal adenoma and B-cell lymphoma. 11,12,30 In the present study, we rst investigated the clinical signicance of miR-320d and explored its role in cell growth, apoptosis, migration and invasion of breast cancer. The results demonstrated that the expression of miR-320d in breast cancer tissues was signi-cantly lower than that in normal tissues.…”
Section: 29mentioning
confidence: 99%